Managing New Industry Creation: Global Knowledge Formation and Entrepreneurship in High TechnologyManaging New Industry Creation: Global Knowledge Formation and Entrepreneurship in High Technology, by MurthaThomas P., LenwayStephanie Ann, and HartJeffrey A.. Stanford, CA: Stanford Business Press, 2001. - Chandran, Jay P. (Academy of Management Review, 2004)
The article reviews the book ?Managing New Industry Creation: Global Knowledge Formation and Entrepreneurship in High Technology,? by Thomas P. Murtha, Stephanie Ann Lenway, and Jeffrey A. Hart.